2014
DOI: 10.1177/0003319714520954
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Neutrophil–Lymphocyte Ratio With the Presence, Severity, and Extent of Coronary Atherosclerosis Detected by Coronary Computed Tomography Angiography

Abstract: We evaluated whether the neutrophil-lymphocyte ratio (NLR) was associated with the presence, severity, and extent of coronary atherosclerotic plaques detected by computed tomography angiography (CTA). We studied 238 patients who underwent dual-source 64-slice CTA for the assessment of coronary artery disease. Coronary arteries were evaluated on 16-segment basis and critical plaque was described as luminal narrowing >50%. In regression analysis, being in the third NLR tertile increased the risk of coronary athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 30 publications
1
25
0
1
Order By: Relevance
“…Our findings confirm the results reported by Kaya et al, in 186 patients undergoing coronary angiography, where NLR was related to the complexity of CAD assessed by SYNTAX score. 49 Similar conclusion was reached by Altun et al, 50 in a Scandinavian cohort of 287 patients with ACS, and by Açar et al 51 in 283 patients evaluated by coronary computed tomography, where NLR values in the third tertile increased the risk of CAD and the severity of critical luminal stenosis. Therefore, the present study provides a deeper insight into the stratification tools for assessing the risk of CAD and in the role of immune response in the pathogenesis of CAD, suggesting the hypothesis of immune modulation as a potential pharmacological target for the prevention of CV disease.…”
Section: Discussionsupporting
confidence: 65%
“…Our findings confirm the results reported by Kaya et al, in 186 patients undergoing coronary angiography, where NLR was related to the complexity of CAD assessed by SYNTAX score. 49 Similar conclusion was reached by Altun et al, 50 in a Scandinavian cohort of 287 patients with ACS, and by Açar et al 51 in 283 patients evaluated by coronary computed tomography, where NLR values in the third tertile increased the risk of CAD and the severity of critical luminal stenosis. Therefore, the present study provides a deeper insight into the stratification tools for assessing the risk of CAD and in the role of immune response in the pathogenesis of CAD, suggesting the hypothesis of immune modulation as a potential pharmacological target for the prevention of CV disease.…”
Section: Discussionsupporting
confidence: 65%
“…Among 17 studies of 8,988 subjects, 4 studies [ 14 , 16 , 20 , 23 ] reported ORs of high versus low NLR, 8 studies [ 10 12 , 17 , 19 , 21 , 22 , 26 ] reported mean differences of NLR between CAD and non-CAD patients, and 5 studies [ 13 , 15 , 18 , 24 , 25 ] reported both.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several studies showed a relationship between low lymphocyte count and malnutrition [24, 25]. Thus, the combination of elevated neutrophils (nonspecific inflammation) and decreased levels of lymphocytes (regulatory component) into a single composite marker may provide additional information to interpret the pathogenesis of arterial stiffness [26]. However, there is an ongoing debate whether NLR is merely a surrogate marker of understanding inflammation, or whether it confers an increased risk per se [20].…”
Section: Discussionmentioning
confidence: 99%